Artificial Intelligence: A Catalyst for Sustainable Development Goals of Health Care, Quality Education and Climate Action - Banerjee, Nandini; Rakshit, Susmita (Exploration अन्वेषण, 2026)
Artificial Intelligence (AI) has become an avant-garde with high potential to guide, monitor and accelerate the fulfilment of Sustainable Development Goals (SDGs). The considerable role of AI to achieve three significant SDGs: SDG 3 (Good Health and Well-being), SDG 4 (Quality Education) and SDG 13 (Climate Action) are comprehensively explored by this study. This study employs a systematic thematic analysis of relevant literature reviews on the role of AI in healthcare, quality education, and climate action taken from different academic databases. Strict inclusion criteria were included to prioritise the studies. Non-academic, technical and irrelevant studies were not taken into account. A total of 25 studies are thoroughly examined to identify the main patterns, themes and trends. The review follows systematic steps, which include repeated familiarisation with the literature, coding, refinement, and synthesis. Finally, the report highlights how AI incorporation increases the quality of healthcare, education and climate activities. This would raise awareness the learners and commoners about the ethical use of artificial intelligence, highlighting health care, quality education, and climate action. The appropriate use of AI should remove the barrier of the digital divide to let all learners access the AI tools. Proper utilisation of the same should focus on the most beneficial way of medical care. It should not cause damage to the environment.